Inside sales social media use and its strategic implications for salesperson-customer digital engagement and performance / Muhammad Khairul Adli Ahmadie - Ahmadie, Muhammad Khairul Adli (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
This article is about how inside salespeople's "lived experiences" and their connection with social media in sales were investigated using a grounded theory method. In business, social media allows anybody to offer an opinion or an idea at any point along the company's road to market. Individuals create, distribute, and share material on social media sites. Brands may have conversations and interactions with individual followers via social networking platforms. This one-on-one engagement can help followers and potential customers develop and strengthen brand loyalty. Based on the article, the researchers explained that inside sales are becoming increasingly important. Buyers' preferences are shifting away from face to-face meetings and toward virtual relationships, creating a bright future for inside salespeople who use social media. Remote selling attempts employing one or more digital technical tools without the use of traditional face-to-face interactions with customers are known as inside sales (Seley & Holloway, 2008).